PROJECT WORK IN FOREIGN LANGUAGE TEACHING AND LEARNING - Danilova, V.V.; Bermuhambetova, A.A.; Assanova, A.B.; Ungutbaeva, G.S. (PUBLISHINGS of Kostanay State Pedagogical University, 2019)
The problem of using project work in teaching English is of great importance. Project work is characterized as one of the most effective methods of teaching and learning a foreign language through research and communication, different types of this method allow us to use it in all the spheres of the educational process. The main idea of project work is considered to be based on teaching students through research activities and stimulating their personal interest.
Keywords: project work; effective method; research activity; educational process